2021
DOI: 10.5009/gnl210311
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Agonists Alter the Pancreatic Cancer Microenvironment by Shifting the Macrophage Phenotype toward M1 and Suppress Human Pancreatic Cancer in Organotypic Slice Cultures

Abstract: Background/Aims: CD40 agonists are thought to generate antitumor effects on pancreatic cancer via macrophages and T cells. We aimed to investigate the role of CD40 agonists in the differentiation of macrophages and treatment of human pancreatic adenocarcinoma.Methods: Immunohistochemistry was performed on paraffin-embedded surgical blocks from patients with pancreatic cancers to evaluate macrophage phenotypes and their relationship with survival. The effects of CD40 agonists on macrophage phenotypes and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…5d, e). We observed that most infiltrated spots highly expressed M1’s marker gene, Cd40 26 , while many peripheral spots did not express it at all (Fig. 5f).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…5d, e). We observed that most infiltrated spots highly expressed M1’s marker gene, Cd40 26 , while many peripheral spots did not express it at all (Fig. 5f).…”
Section: Resultsmentioning
confidence: 91%
“…This result suggests that M1 macrophage is more actively recruited into the tumor center rather than being gated by the boundary, like other immune cell types. Since M1s are anti-tumor macrophages 26 , we believe further investigation of their role in human EMT samples is critical to understanding and facilitating treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 This limitation is primarily because of the degradation and dysfunction of DCs, 2 resulting from the lack of activators in the tumor microenvironment (TME). Agonists or ligands (L) of CD40 induce maturation, enhance the function of DCs, 3 and elicit the generation of antitumoral M1 macrophages from progenitors or pro-tumoral M2 macrophages. 4 Additionally, interferon gamma (IFNγ) activates an antitumoral immune response mediated by mature DCs.…”
Section: Introductionmentioning
confidence: 99%